2015
DOI: 10.1589/jpts.27.837
|View full text |Cite
|
Sign up to set email alerts
|

Relation between functional ability and health-related quality of life of children with juvenile rheumatoid arthritis

Abstract: [Purpose] The aim of this study was to assess patients’ health-related quality of life, compare it with a healthy age-matched population, and examine associations between functional ability and quality of life among juvenile rheumatoid arthritis (JRA) patients. [Subjects and Methods] The study participants were 26 JRA patients and 25 controls. The Childhood Health Assessment Questionnaire and the Pediatric Quality of Life Inventory 4.0 Generic Core Scales were used to evaluate functional ability and health-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…A study carried out in the UK by Shaw et al showed that the difficulties with regular physical activity constitute the greatest issue for half of the adolescents with JIA [7]. Kwon et al [15] reported a high negative correlation ( r = –0.74) between functional ability and overall HRQoL among adolescents with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in the UK by Shaw et al showed that the difficulties with regular physical activity constitute the greatest issue for half of the adolescents with JIA [7]. Kwon et al [15] reported a high negative correlation ( r = –0.74) between functional ability and overall HRQoL among adolescents with JIA.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring age, gender, stroke severity, and baseline functional status, the study showed that health outcome and functional status improved for patients with rehabilitation after six months with a return to near pre‐stroke ability. Kwon, Kim, and Lee, in their qualitative and self‐assessment correlational study, reported the functional ability of patients diagnosed with juvenile rheumatoid arthritis (JRA) was statistically positively correlated ( r = 0.748, p = < .001) with health‐related quality of life. JRA is a long‐term, debilitating condition with physical impairments and symptoms interfering with the ability to function normally at an early age, resulting in a generally poor quality of life for children with JRA .…”
Section: Discussion Of Study Resultsmentioning
confidence: 99%
“…A possible explanation for less attention paid by adolescents with JIA to their dental aesthetic could be due to some aspects related to their daily lives. Indeed, JIA patients usually present a lower physical well-being dimension associated with increased difficulties in performing regular physical activity as compared with healthy subjects [49,50], and this was highly correlated with a lower HRQoL among JIA adolescents [51]. Moreover, these patients are constantly treated for their chronic pathology and they also undergo regular medical consultations due to pain, physical disability and eye-related problems (uveitis) that negatively affect their emotions, their possibility to attend school and their daily activities [52].…”
Section: Discussionmentioning
confidence: 99%